Data Cache-Energy and Throughput Models: Design Exploration for Embedded Processors. (6th December 2009) - Qadri, Muhammad Yasir; McDonald-Maier, Klaus D.
Abstract : Most modern 16-bit and 32-bit embedded processors contain cache memories to further increase instruction throughput of the device. Embedded processors that contain cache memories open an opportunity for the low-power research community to model the impact of cache energy consumption and throughput gains. For optimal cache memory configuration mathematical models have been proposed in the past. Most of these models are complex enough to be adapted for modern applications like run-time cache reconfiguration. This paper improves and validates previously proposed energy and throughput models for a data cache, which could be used for overhead analysis for various cache types with relatively small amount of inputs. These models analyze the energy and throughput of a data cache on an application basis, thus providing the hardware and software designer with the feedback vital to tune the cache or application for a given energy budget. The models are suitable for use at design time in the cache optimization process for embedded processors considering time and energy overhead or could be employed at runtime for reconfigurable architectures.